2006
DOI: 10.1111/j.1464-410x.2006.06191.x
|View full text |Cite
|
Sign up to set email alerts
|

Prostate‐specific Antigen Testing in Hypogonadism: Implications for the Safety of Testosterone‐replacement Therapy

Abstract: Hypogonadal men have lower prostate volumes and serum prostate-specific antigen (PSA) levels than age-matched controls. When present, prostate cancer in hypogonadal men is more aggressive than in eugonadal men, and given the lack of specificity of PSA for diagnosing prostate cancer, a more accurate test would be desirable in hypogonadal men. Once testosterone-replacement therapy is started in hypogonadal men, PSA levels should be measured regularly; however, there is often an initial rise 3-6 months after star… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…16 In healthy volunteers, medical castration, although dramatically reducing serum testosterone and dihydrotestosterone levels, does not abolish intraprostatic levels, and they remain at 20-30%. This may indicate that there is a capacity within the prostate to manufacture and rogens in the face of very low plasma levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 In healthy volunteers, medical castration, although dramatically reducing serum testosterone and dihydrotestosterone levels, does not abolish intraprostatic levels, and they remain at 20-30%. This may indicate that there is a capacity within the prostate to manufacture and rogens in the face of very low plasma levels.…”
Section: Discussionmentioning
confidence: 99%
“…14 IIEF was used to better define the erectile function. The possible scores for the IIEF-5 range from 5 to 25, and ED was classified into five categories based on the scores: severe (5-7), moderate (8)(9)(10)(11), mild to moderate (12)(13)(14)(15)(16), mild (17)(18)(19)(20)(21) and no ED (22)(23)(24)(25). 15 …”
Section: Hrqol Measuresmentioning
confidence: 99%
“…According to Endocrine Society guidelines, men with a PSA level .4 ng/ml or with a high risk of prostate cancer and a PSA level .3 ng/ml are recommended to be referred to a urologist prior to initiation of testosterone therapy. 18,28 It is possible that the low rates of PSA screening may be attributable to some physicians' concerns about overscreening for prostate cancer. Previous research has reported that such overscreening may lead to overdiagnosis of prostate cancer, which can result in excess biopsies and unnecessary treatment.…”
Section: Discussionmentioning
confidence: 99%
“…67,68 In hypogonadal men, PSA levels are often low, which normalize after TRT, but do not continue to increase with continued therapy, 21,69 and prostate volume returns essentially to that of eugonadal men but no higher. 70 In Swerdloff 's study 71 of 166 hypogonadal men, 3 years of TRT resulted in a mean serum PSA increase of 0.37 ng/ml and a 1.8% incidence of biopsy-proven prostate cancer (three men).…”
Section: Biological Influence Of Trtmentioning
confidence: 91%